Seroprevalence Of Hepatitis B, Hepatitis C And HIV 1 / 2 IN Patients Undergoing Surgery In A Tertiary Care Hospital - Agarwal, Sheetal; Agarwal, Akshat; Azam, Shahanwaz; Singh, Dinesh Kumar; Soni, Edamakanti Swetha; Afaq, Nashra; Singh, Anurag; Kumar, Pankaj (Journal of Neonatal Surgery, 2025)
Introduction: Hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) are significant global health threats that share common routes of transmission, especially through contaminated blood and surgical procedures. Identifying seroprevalence in patients undergoing surgery is essential to minimize occupational exposure and provide timely medical intervention. Screening for HIV, Hepatitis B, and Hepatitis C in patients having elective surgery was the study's goal in order to decrease transmission to healthcare professionals and offer preventive and treatment services. Aim and Objective: To study the seroprevalence of hepatitis B, hepatitis C and HIV 1 / 2 in patients undergoing surgery in a tertiary care hospital Materials and methods: The study involved the recruitment of patients scheduled for elective surgery, who were screened for HBs Ag and antibodies to HIV 1/2 and hepatitis C, respectively, using coomb AID, a rapid immunoassay test, to identify the antibodies to HIV 1/2, and SD HBs Ag ELISA 3.0 and SD HCV ELISA 3.0 to detect HBs Ag and IgG antibodies to HCV, respectively. Results: The prevalence of HBV and HCV infection, respectively, was 1.91% and 1.05% in our study. Three individuals (0.03%) tested positive for both HBV and HCV. HIV was not detected in any of the individuals. Conclusion: Surgical patients have a high seroprevalence of viral infections with hepatitis B and hepatitis C. Risk factors include not taking pre- and postoperative precautions, using infected syringes and surgical instruments again, and more.